Penerapan Pembelajaran Think Talk Write Untuk Meningkatkan Hasil Belajar Matematika - Rahmatina Aulia; Nahor Murani Hutapea; Syofni Syofni (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
This study aims to improve the learning process and the student’s mathematical result by applying Think-Talk-Write strategy in cooperative learning. The research subject were 34 students of class VIII1 SMPN 12 Pekanbaru. This study was conducted in the odd semester of the academic year 2019/2020. This research is Classromm Action Research with two cycles and each of cycle has four stages: planning, implementation, observation, and reflection. Data in this research are teacher and student activity sheets and student’s mathematical result data. The research instuments consists of learning device (Syllabus, Lesson Plans, and Student Activity Sheets) and instruments for data collecting (teacher and students observation sheet and mathematics learning outcome test). The data analysis technique used is descriptive narrative analysis which is done by describing the data collected on the observation sheet. Based on analysis of teacher and student activity sheets was obtained that implementation of learning process on cycle II better than cycle I. The results of this research showed an increasing the number of students who reach the Minimum Completeness Criteria from the base score to cycle I and cycle II. The number of students who reached Minimum Competeness Criteria on the base score was 8 person, in cycle I was 17 person and in cycle II was 27 person. Results of this research indicates that the implementation of Think-Talk-Write strategy in cooperative learning to improve the learning process and improve the student’s mathematics result at class VIII1 SMPN 12 Pekanbaru.